Re: How to monitor pregnancies complicated by fetal growth restriction and delivery before 32 weeks: post‐hoc analysis of TRUFFLE study. W. Ganzevoort, N. Mensing Van Charante, B. Thilaganathan, F. Prefumo, B. Arabin, C. M. Bilardo, et al., on behalf of the TRUFFLE Group. Ultrasound Obstet Gynecol 2017; 49: 769–777. (June 2017) - Schenone, M.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 49: 769–777